2012
DOI: 10.1128/jvi.06233-11
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of 21 Varicella-Zoster Virus Genomes Reveals Two Novel Genotypes and Evidence of Recombination

Abstract: Genotyping of 21 varicella-zoster virus (VZV) strains using a scattered single nucleotide polymorphism (SNP) method revealed ambiguous SNPs and two nontypeable isolates. For a further genetic characterization, the genomes of all strains were sequenced using the 454 technology. Almost-complete genome sequences were assembled, and most remaining gaps were closed with V aricella-zoster virus (VZV) is a member of the genus Varicellovirus within the subfamily Alphaherpesvirinae, family Herpesviridae (8). The alphah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 61 publications
(92 reference statements)
0
85
1
1
Order By: Relevance
“…It is possible that EHV-1 recombination events may have occurred but were not able to be detected at the required level of statistical significance, because an insufficient number of SNPs specific for the parental viruses were transferred to the recombinant viruses. However, evidence of frequent, natural recombination has been readily detected in VZV, which also has a highly conserved genome (approximately 30-200 SNP differences between any two strains), using similar methods to those in this study (Norberg et al, 2015(Norberg et al, , 2006Zell et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that EHV-1 recombination events may have occurred but were not able to be detected at the required level of statistical significance, because an insufficient number of SNPs specific for the parental viruses were transferred to the recombinant viruses. However, evidence of frequent, natural recombination has been readily detected in VZV, which also has a highly conserved genome (approximately 30-200 SNP differences between any two strains), using similar methods to those in this study (Norberg et al, 2015(Norberg et al, , 2006Zell et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Only a single, fully sequenced clade 9 isolate (JN704710) had been previously identified and described in the literature [4]. The complete genome sequence for the KPSC study isolate (KY037798) identified in this study fulfilled the requirement for redesignating provisional clade IX as established clade 9.…”
Section: Discussionmentioning
confidence: 80%
“…All 102 publicly available VZV WGSs (or nearly complete genomic sequences) were downloaded from GenBank (search 10 May 2016). The WGSs were analysed using the analysis scheme developed by Zell and coworkers [4], specifically, limiting analyses to unique sequences. The genome sequence was divided into eight distinct regions (A to H), as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation